2022
DOI: 10.3390/rs14030640
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Monitoring of Submerged Aquatic Vegetation in a Macrophytic Lake Using Time-Series Sentinel-2 Images

Abstract: Submerged aquatic vegetation (SAV) is one of the most important biological groups in shallow lakes ecosystems, and it plays a vital role in stabilizing the structure and function of water ecosystems. The study area of this research is Baiyangdian, which is a typical macrophytic lake with complex land cover types. This research aims to solve the low accuracy problem of the remote sensing extraction of SAV, which is mainly caused by water level fluctuations, differences in life-history characteristics, and mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Several studies have shown high denitrification rates in wetlands, related to temporal water retention [92][93][94]. Unlike other studies [95][96][97], the mean NDVI values of the VI in NREGUs in our study were below 0.6 in all seasons, because the study area consisted of only low growing vegetation, without trees or shrubs. Therefore, over saturation of NDVI due to dense vegetation might not be considered a hindrance for the present research and provides the effectiveness of NDVI over EVI.…”
Section: Discussioncontrasting
confidence: 79%
“…Several studies have shown high denitrification rates in wetlands, related to temporal water retention [92][93][94]. Unlike other studies [95][96][97], the mean NDVI values of the VI in NREGUs in our study were below 0.6 in all seasons, because the study area consisted of only low growing vegetation, without trees or shrubs. Therefore, over saturation of NDVI due to dense vegetation might not be considered a hindrance for the present research and provides the effectiveness of NDVI over EVI.…”
Section: Discussioncontrasting
confidence: 79%
“…For example, Ghirardi et al (2022) [161] and Xia et al (2022) [162] explored the decade scale of SAV dynamics using remote sensing images, providing a reference area for restoration. The classification accuracy of SAV changed from 60% to nearly 95% in existing studies [158,[163][164][165], which were mainly limited by the resolution of images, water depth, water color, and spectral traits of specific submerged macrophytes [158,166]. With the increase in the resolution of satellite images, the dynamics of specific aquatic macrophyte species can also be interpreted.…”
Section: Remote Sensingmentioning
confidence: 97%
“…Optional monitoring can be implemented (e.g. spawning monitoring can estimate the number of eggs laid by the different species on the introduced substratum (Dumonceau & Gilles, 2012); aerial photo monitoring can help to visualize changes in habitat and plant community types through photointerpretation analysis (Liang et al, 2022; Lyon & Drobney, 1984; Wilcox & Bateman, 2018)).…”
Section: Sampling Plan and Operational Standardized Protocolsmentioning
confidence: 99%